2011
DOI: 10.1111/j.1365-263x.2011.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of school‐based dental programme on dental caries experience in Yogyakarta Province, Indonesia

Abstract: The study suggests that the differences in DMFT of children in good and poor performance SBDPs were caused by relation to social factors rather than by relation to oral health service activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 16 publications
5
24
0
3
Order By: Relevance
“…Schools were encouraged to have a policy regarding their children's oral health and to subsequently establish oral health-related activities or environments in schools. Studies on oral health-promoting schools were conducted in many countries, such as Indonesia, Taiwan, China, New Zealand, Nigeria, Finland, and Thailand [Petersen et al, 2001[Petersen et al, , 2004[Petersen et al, , 2015Tai et al, 2009;Anttonen et al, 2011;Amalia et al, 2012;Esan et al, 2015;Lai et al, 2016;Thornley et al, 2017]. Examples of the oral health supportive activities or environments established in schools were oral health education taught by professionals, oral health education integrated into the school curriculum and taught by school teachers, simple oral examinations conducted by teachers, toothbrushing after lunch, free toothbrushes and toothpaste (toothbrushing materials) for children, restricting sugary and junk food in schools, and providing vegetables and fruit in school meals [Kwan et al, 2005].…”
mentioning
confidence: 99%
“…Schools were encouraged to have a policy regarding their children's oral health and to subsequently establish oral health-related activities or environments in schools. Studies on oral health-promoting schools were conducted in many countries, such as Indonesia, Taiwan, China, New Zealand, Nigeria, Finland, and Thailand [Petersen et al, 2001[Petersen et al, , 2004[Petersen et al, , 2015Tai et al, 2009;Anttonen et al, 2011;Amalia et al, 2012;Esan et al, 2015;Lai et al, 2016;Thornley et al, 2017]. Examples of the oral health supportive activities or environments established in schools were oral health education taught by professionals, oral health education integrated into the school curriculum and taught by school teachers, simple oral examinations conducted by teachers, toothbrushing after lunch, free toothbrushes and toothpaste (toothbrushing materials) for children, restricting sugary and junk food in schools, and providing vegetables and fruit in school meals [Kwan et al, 2005].…”
mentioning
confidence: 99%
“…Each root was cut off from the tooth, resulting an intact crown. Then, each crown was cut into a 6 cm 3 block. An unvarnished occlusal surface window was created for each of these 40 tooth blocks by covering each occlusal surface with a 3x5 mm 2 sticker and painting all other surfaces with an acid-resistant varnish.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies assessed the effectiveness of the Indonesian school-based dental program in controlling caries, which suggested that the Decayed Missing Filling Teeth (DMF-T) scores of children were related to social factors rather than to oral health service activities in the school program. 3,4 Therefore, an intervention program that is applicable, effective, feasible, sustainable and acceptable by the Indonesian community is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However, studies conducted in China, Indonesia, Brazil and Iran show positive results. [6][7][8] The importance and value of the impact of school-based interventions on children has been identified in SA.…”
mentioning
confidence: 99%